Radiotracer studies to isolate in-house receptors from poultry liver for multi-chemical hazard analysis in selected food and feed. Issue 10 (3rd October 2022) - Maqbool, Uzma; Sasanya, James; Shah, Muhammad Salahuddin; Chughtai, Muhammad Ismail; Hussain, Ghulam
Abstract: In-house receptors (IHRs) were isolated from non-immunized poultry liver to analyze selected contaminants and residues in targeted food and feed using 14 C- and 3 H-labeled radiotracers. Matrix (2 g) was homogenized and centrifuged with the resultant pellet used as IHRs. These were characterized for total protein contents (6.1 mg mL −1 ) and compared with commercial receptors for aflatoxins (0.28 mg tablet −1 ) and chloramphenicol (0.12 mg tablet −1 ). Gel electrophoresis of the IHRs showed a mixture of polypeptides—an important attribute for multi-residues analysis—compared with commercial receptors that presented specific protein bands at 65 kDa (chloramphenicol) and 70 kDa (aflatoxins). The inhibition index of IHRs for aflatoxins B1 and B2 in wheat and bovine feed and chloramphenicol in bovine tissue at, above, and below maximum limits or minimum required performance limits, revealed an inverse relationship between radiotracer and analyte concentrations. Saturation with increased radioligand concentration up to 5.5 kBq indicated higher holding potential. However, increasing incubation time to 30 min did not significantly increase analyte-binding. The IHRs performance was comparable to commercial receptors with control point averages of 348, 410, 555, and 307 counts per minute determined for gentamicin, chloramphenicol, oxytetracycline, and aflatoxin M1, respectively in local milk samples.